Impact Of Dysmenorrhea Management Health Education On Adolescent Girls' Knowledge And Attitude About Dysmenorrhea Management - Puji Astuti, Retno; Evita Muslima Isnanda Putri; Rahmawati, Rahmawati; Untari, Nurdiana (Sean Institute, 2024)
Dysmenorrhea can cause various problems, such as disrupting their activities as students. Knowledge and attitudes can be important factors for adolescent girls in managing dysmenorrhea. The purpose of this study is to analyze the effect of health education on dysmenorrhea management on the knowledge and attitudes of adolescent girls in managing dysmenorrhea. This study employed a pre-experimental design with a one-group pre-test post-test approach. The population consisted of all female students in grades VII-IX at SMP Muhammadiyah 5 Randublatung, Blora Regency, in 2022, totaling 31 students. The sample included 31 respondents, selected through total sampling technique. The independent variable was health education on dysmenorrhea, and the dependent variables were knowledge and attitudes about dysmenorrhea and its management. Data were collected using a questionnaire. Data processing involved editing, scoring, coding, tabulating, and analyzing data using cross-tabulation. The study results showed that before the health education intervention, 16 respondents (51.6%) had moderate knowledge, and 19 respondents (61.3%) had a favorable attitude. After the health education intervention, 18 respondents (58.1%) had moderate knowledge, and 26 respondents (83.9%) had a favorable attitude. There was an effect of health education on dysmenorrhea management on the knowledge and attitudes of adolescent girls in managing dysmenorrhea.